Analysis of the Translation of the Song “Water Under the Bridge” by Adeke’s Version - Safitri, Diya; Syahrial, Syahrial; Maisarah, Ira (Linguistic, English Education and Art (LEEA) Journal, 2023)
This study aims to describe the translation strategy applied to translate the lyrics of the song "Water Under the Bridge" from English to Indonesian (https://translation-lirik-lagu-barat.blogspot.com/2015/12/water-under -bridge-adele.html) and to explain the quality of the translation in terms of correctness and acceptance of its meaning according to the original text. The method used is descriptive qualitative research; the data and data sources are the results of translating the song lyrics, and the research instruments used are documents and questionnaires. The research results show that based on the information data, the strategy used in the process of translating is a phonemic translation (25%), verse into process translation (25%), and interpretation (25%), which is often used in translating Adele's songs. It can be concluded that the method used is more oriented towards the target language because the use of translation techniques is more oriented towards the use of the target language. The overall results of the translation quality of songs in the accuracy category are inaccurate (1%), less accurate (33%), and accurate (66%). Meanwhile, the acceptability category is inaccurate (2%), less accurate (43%), and accurate (55%). So, the quality of the translation in the category of accuracy and acceptability of the translation is good according to the target language. Keywords: Translation of song lyrics, Translation quality, Translation strategy